Law of the European Union - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (My University, 2016)
This Textbook makes an integral part of the TEMPUS InterEULawEast project No . 544117 funded by the European Union aiming at ensuring the sustainability and visibility of the project after its completion. Documents are issued as of January 1, 2016. It is written for teahers and students of law schools and faculties, law enforcement officials.

Цей підручник є невід'ємною частиною проекту TEMPUS InterEULawEast № 544117, що фінансується Європейським Союзом, спрямований на забезпечення стійкості і наочності проекту після його завершення.

Этот учебник является неотъемлемой частью проекта TEMPUS InterEULawEast № 544117, финансируемого Европейским Союзом, направленный на обеспечение устойчивости и наглядности проекта после его завершения.
a Textbook for Master Students
Law of the European Union: a Textbook for Master Students / ed. P. Biriukov and V. Tuliakov. - Voronezh: VSU Publishing House, 2016. - 476 p.
Keywords: the history of the European Union; objectives of the European Union; principles of the European Union; competences of the European Union; enhanced cooperation in the European Union; introduction to the European Union law; sources of law of the European Union; Law-making in the European Union; international law; European Union institutions; European Court system; історія Європейського Союзу; цілі Європейського Союзу; принципи Європейського Союзу; компетенція Європейського союзу; розширення співпраці в Європейському Союзі; членство в Європейському Союзі; джерела права Європейського Союзу; правотворчість в Європейському Союзі; міжнародне право; установи Європейського союзу; Європейська система суду; история Европейского Союза; цели Европейского Союза; принципы Европейского Союза; компетенция Европейского союза; расширение сотрудничества в Европейском Союзе; источники права Европейского Союза; правотворчество в Европейском Союзе; международное право; учреждения Европейского союза; европейская система суда